2021
DOI: 10.1891/jnm-d-20-00140
|View full text |Cite
|
Sign up to set email alerts
|

Translation and Validation of the Comprehensive Score of Financial Toxicity for Cancer Patients Into Arabic

Abstract: Background and PurposeWe aimed to translate the Comprehensive Score of Financial Toxicity (COST) questionnaire into Arabic and to evaluate its reliability and validity.MethodsWe applied the four-step translation method and conducted a pilot validation study over 179 medical oncology patients. Reliability was tested using the Cronbach alpha coefficient and test–retest stability. Validity was tested using the correlation with Functional assessment of Cancer Therapy-General score (FACT-G), factorial analysis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Interestingly, our included studies showed that the correlation strengths between financial toxicity and overall HRQOL were slightly stronger in studies that used English instruments (median = 0.53, range = 0.33-0.73) 57,58,60,62,64,66,73,81 than those in other languages, for example, Mandarin Chinese, Italian, and Arabic (median = 0.43, range = 0.34-0.52), 51,55,67,72,79,80 and conducted in countries with universal health coverage (median = 0.49, range = 0.34-0.73) 55,58,66,72,79,80 than those without (median = 0.42, range = 0.33-0.63). 51,57,60,62,64,67,73,81 Nevertheless, we had inadequate number of studies to further examine (eg, performing subgroup analysis) the potential impact of instrument language or universal health coverage on the association between financial toxicity and HRQOL. 46 Exploring the role of universal health coverage and mitigation strategies in alleviating financial toxicity and improving HRQOL may be an important future research direction.…”
Section: Discussionmentioning
confidence: 86%
“…Interestingly, our included studies showed that the correlation strengths between financial toxicity and overall HRQOL were slightly stronger in studies that used English instruments (median = 0.53, range = 0.33-0.73) 57,58,60,62,64,66,73,81 than those in other languages, for example, Mandarin Chinese, Italian, and Arabic (median = 0.43, range = 0.34-0.52), 51,55,67,72,79,80 and conducted in countries with universal health coverage (median = 0.49, range = 0.34-0.73) 55,58,66,72,79,80 than those without (median = 0.42, range = 0.33-0.63). 51,57,60,62,64,67,73,81 Nevertheless, we had inadequate number of studies to further examine (eg, performing subgroup analysis) the potential impact of instrument language or universal health coverage on the association between financial toxicity and HRQOL. 46 Exploring the role of universal health coverage and mitigation strategies in alleviating financial toxicity and improving HRQOL may be an important future research direction.…”
Section: Discussionmentioning
confidence: 86%